Pengaruh Struktur Modal Terhadap Nilai Perusahaan Dimoderasi Good Corporate Governance Dan Corporate Social Responbility (Studi Pada Perusahaan Pertambangan Yang Go Public Di Bursa Efek Indonesia 2021 -2023) - Lestari, Siswi Muji; Mardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to examine the influence of capital structure on company value moderated by good corporate governance and corporate social responbility. The population in this research is mining sector companies listed on the Indonesia Stock Exchange (BEI) in the period 2021 to 2023. Using Purposive sampling method, a sample size of 11 mining sector companies was obtained, so the total obesrvations is secondary. The Moderated Regression Analysis (MRA) analysis techique is used to test whether the interaction between independent variables and moderating variables has an effect on the dependent variable. The result of this research show that capital structure as measured by DER has a significant influence on company value. Good Corporate Governance and Corporate Social Responbility are unable to moderate the influence of company size on company value. Keywords: Capital Structure, Good Corporate Governance, Corporate Social Responbility, Company Value.